REHABILITASI SOSIAL BAGI PENYANDANG DISABILITAS INTELEKTUAL MELALUI SHELTERED WORKSHOP PEDULI (SWP) BASKARA DI DESA GEBYOG OLEH DINAS SOSIAL KABUPATEN MAGETAN - Muhammad Khoirul Ichwan; Galih Wahyu Pradana (Universitas Negeri Surabaya, 2022)
The Kartini Social Rehabilitation Center for People with Intellectual Disabilities (BBRSPDI) in Temanggung is in collaboration with the Social Service of Magetan to organize non-institutional social rehabilitation program for people with intellectual disabilities, focusing on productive economic activities to achieve independence and create an inclusive environment. This study aims to describe the process of social rehabilitation for persons with intellectual disabilities through SWP Baskara in Gebyog Village. The focus in this study uses the theory of empowerment of the EPE (Engagement-Participation-Empowerment), consisting of four stages of empowerment, namely (i) exogenous, (ii) exogenous and endogenous, (iii) endogenous and exogenous. (iv) endogenous. Data was collected through interviews, observations and documentation study of secondary data related to the topic. The data analyzed descriptively qualitative. The results showed that the implementation of rehabilitation through SWP Baskara had a positive impact on persons with intellectual disabilities/beneficiaries in Gebyog Village, both from a social and economic perspective. Suggestions from this research are the need to develop splashed batik both in terms of products and marketing in order to increase competitiveness. In addition, increasing accessibility for persons with intellectual disabilities/beneficiaries living outside Gebyog Village is also important so that they routinely participate in activities at SWP Baskara.